The Role of Religious Moderation in Good Governance in Indonesia’s Democratic Era: An Analysis of the Film Tanda Tanya (?) - Della Dwi Hidayah Kurnia Putri; Raden Ajeng Intan Nuraini Febriana; Putra Adi Kustiyan; Raihan Nafis Pratama; Siti A’immatul Farida; Hendrik Feranata Al Rahmat (Jurnal Indonesia Studi Moderasi Beragama, 2026)
Background: Indonesia’s cultural diversity creates complex challenges for sustaining religious harmony. The film Tanda Tanya (?) depicts interfaith interactions and social tensions that reflect these challenges in contemporary Indonesian society. Objective: This study examines how the film represents religious moderation and principles of good governance, emphasising the relationship among individual behaviour, community values, and social stability. Method: A qualitative content analysis was conducted, focusing on scenes, dialogues, character interactions, and conflict patterns to identify indicators of moderation and governance practices. Results: The film illustrates tolerance, interfaith cooperation, non-violence, and respect for human dignity, alongside community participation, fairness, and rejection of discrimination. Unresolved conflicts in the narrative reveal vulnerabilities and social tensions when moderation values are absent. Conclusion: Religious moderation provides a foundation for inclusive, stable, and effective social governance, while its absence can lead to imbalance and conflict. Contribution: This study highlights how film can serve as a reflective and educational medium, offering insights and strategies to promote religious moderation and support good governance in Indonesia’s multicultural public sphere.